2018
DOI: 10.3390/ma11050814
|View full text |Cite
|
Sign up to set email alerts
|

3-[Bis(pyridin-2-ylmethyl)amino]-5-(4-carboxyphenyl)-BODIPY as Ratiometric Fluorescent Sensor for Cu2+

Abstract: We developed an asymmetric fluorescent sensor 1 for Cu2+, based on 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY), by introducing 4-carboxyphenyl and bis(pyridin-2-ylmethyl)amine groups at the 5- and 3-positions, respectively, of the BODIPY core. We then investigated the photophysical and cation-sensing properties of the sensor. BODIPY 1 showed large absorption and fluorescence spectral shifts on binding to Cu2+. The fluorescence peak at 580 nm red-shifted to 620 nm. The binding stoichiometry of BODIPY 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…DPA-based sensors for Cu 2+ with several different fluorophores have been reported, including ruthenium (II) [7,8] and iridium (II) [9] complexes, naphthalimide [10][11][12], chalcones [13] and BODIPY dyes [14,15], among others [16].…”
Section: Introductionmentioning
confidence: 99%
“…DPA-based sensors for Cu 2+ with several different fluorophores have been reported, including ruthenium (II) [7,8] and iridium (II) [9] complexes, naphthalimide [10][11][12], chalcones [13] and BODIPY dyes [14,15], among others [16].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Their exceptional photophysical properties, strong UV-absorbance, sharp fluorescence emission peaks, good solubility in numerous solvents, relative insensitivity towards polarity and pH variation along with rational stability under physiological conditions, make from these fluorescent dyes apposite agents for heavy metal and pesticide recognition. [31][32][33][34] Although numerous examples of cavitand derivatives have been reported in literature, few studies on these two groups (cavitand + BODIPY) combined are reported, [35][36][37][38] and to the best of our knowledge, there have been no report thus far describing the utility of such ionophore-fluorophore conjugates for heavy metal and pesticide recognitions on the cavitand derivatives.…”
Section: Introductionmentioning
confidence: 99%